2020
DOI: 10.1021/acs.biochem.0c00027
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Techniques for Distinguishing Ligand Binding Modes in Cytochrome P450 Monooxygenases

Abstract: The new agreement specifically addresses what authors can do with different versions of their manuscripte.g. use in theses and collections, teaching and training, conference presentations, sharing with colleagues, and posting on websites and repositories. The terms under which these uses can occur are clearly identified to prevent misunderstandings that could jeopardize final publication of a manuscript (Section II, Permitted Uses by Authors).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 75 publications
1
42
1
Order By: Relevance
“…According to one review report [ 3 , 51 , 52 ], all CYPs were different with different activities, and their functional properties were substrate-dependent. The user can swap the active sites to get the desired function from CYPs [ 53 ]. Rowland et al [ 54 ] reported the crystal structure of CYP2D 6 at the resolution of 3A° and noted that the primary structure of the CYP2D 6 is resampled with other CYPs .…”
Section: Discussionmentioning
confidence: 99%
“…According to one review report [ 3 , 51 , 52 ], all CYPs were different with different activities, and their functional properties were substrate-dependent. The user can swap the active sites to get the desired function from CYPs [ 53 ]. Rowland et al [ 54 ] reported the crystal structure of CYP2D 6 at the resolution of 3A° and noted that the primary structure of the CYP2D 6 is resampled with other CYPs .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a spectral difference in the band between substratebound and unbound forms. Papaverine-bound spectra showed a Soret band at 322 nm, which was not observed in the binding of 4-(pyridine-3-yl) benzoic acid and 4-(pyridine-2-yl) benzoic acid to CYP199A4 (Podgorski et al, 2020). This is the first report of N-oxidation of a compound by bacterial CYP.…”
Section: Functional Characterization Of Cyp105d18mentioning
confidence: 71%
“…Even though THP was catalyzed by CYP105D18 using H 2 O 2 as cosubstrate, there was no spin-shift observed. The binding of 4-(pyridine-3-yl) benzoic acid and 4-(pyridine-2-yl) benzoic acid to CYP199A4 exhibits type II UV-vis spectral changes showing a greater shift in the Soret wavelength (422 versus 424 nm) (Podgorski et al, 2020). Papaverine was also modified in the pyridine ring (N-oxidation) by CYP105D18 and exhibits a similar pattern of spectral shift at 422 nm.…”
Section: Functional Characterization Of Cyp105d18mentioning
confidence: 98%
“…In the presence of VBA, there is a significant positive shift in the Fe III/II redox potential relative to the substrate-free redox potential, ΔE = +203 mV (Figures 1d and S2). This positive shift in redox potential is smaller than that measured for 4-methoxybenzoic acid [ΔE = +250 mV, 4-methoxybenzoic acid-bound CYP199A4 and substrate-free CYP199A4 have redox potentials of −188 and −438 mV, respectively, vs normal hydrogen electrode (NHE)], 63 which conforms with the greater spin state shift induced by 4-methoxybenzoic acid. ΔE has been linked to the extent of the displacement of the aqua ligand and associated outer sphere water molecules from the ferric heme, which favors reduction and has been proposed to gate the commencement of the catalytic cycle.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Anisotropic proton hyperfine coupling ridges characteristic of aqua ligands are visible in the weak coupling quadrant (top right, +,+ quadrant). The HYSCORE spectrum for 4methoxybenzoic acid has been reported previously 63.…”
mentioning
confidence: 99%